Rancang Bangun Aplikasi Validasi Desa Berbasis Web Menggunakan Metode Rational Unified Process - Sutedi, Ade; Permana, Dimas Satia (Institut Teknologi Garut, 2025)
This study aims to develop a web-based village validation application in Sindangsuka Village, Cibatu District, Garut Regency, to improve administrative letter services. The background for this development is based on the limitations of the previous system, which could only be accessed via computers at the village office, making it difficult for residents who live far from the location. The development method used is the Rational Unified Process (RUP), which consists of four stages: Inception, Elaboration, Construction, and Transition. The research resulted in an application equipped with features for submitting documents, verification, digital signature validation, and management of village device accounts. Testing was conducted through alpha testing using the blackbox method and beta testing using the System Usability Scale (SUS). The alpha testing results showed that all features functioned as expected, while the beta testing yielded an SUS score of 82 points, categorized as good, proving that the application is suitable for supporting online village administrative services.